RETRACTED: Chemotherapy-induced broadly reactive autoantibodies in the treatment of malignancies - E. V. Shanina; F. Breker; N. A. Lysov; V. Yu. Shanin; Yu. V. Ponomareva; A. A. Supil'nikov (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
RETRACTED ARTICLEThe aim of the study was to evaluate the relationship between chemotherapy and autoimmune reactions in patients with metastatic colorectal cancer. Cancer and autoimmunity are known to be interrelated, but until now it has been unclear to what extent chemotherapy specifically contributes to autoimmune reactions. We studied immunoglobulin M (IgM) levels in response to the administration of various human tissues before and during adjuvant chemotherapy. Patients received seven cycles of chemotherapy with the FOLFIRI plus cetuximab regimen. IgM levels against the tested tissues increased already after the first cycle of chemotherapy and continued to increase during the second and third cycles. Autoimmune responses then began to decrease from the fourth to seventh cycles, but remained elevated from baseline for most of the study tissues. Our results suggest that chemotherapy can induce a wide range of autoimmune reactions. Monitoring self-reactive IgM responses during treatment may help prevent or alleviate side effects associated with autoimmunity.